2007
DOI: 10.1183/09031936.00051406
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and functional changes over 3 years in young children with cystic fibrosis

Abstract: The aim of the present study was to evaluate airway disease progression assessed by chest radiology, expiratory interrupter resistance (Rint,exp) and spirometry in young children with cystic fibrosis (CF) over a 3-yr period.Two chest radiographs combined with two Rint,exp measurements were performed with a 3-yr interval in 21 preschool children (age (mean¡SD) 3.2¡0.9 yrs) and 30 schoolchildren with CF (age 7.2¡1.9 yrs). Chest radiographs were scored using five different CF scoring systems and Rint,exp measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…There are several studies of Rint in children with CF (39,(65)(66)(67)(68)(69)(70), but only three involving children under 6 years of age (39,67,70). Although one study found a reasonable correlation between Rint and other lung function indices (sRaw, FEV 1 , FEF 25-75 ) (66), most studies have shown that Rint measurements do not distinguish health from disease, either at baseline (39,66,(68)(69)(70) or after BD (39,67,69). In addition, two longitudinal studies in 21 (70) and 30 (39) preschool children with CF and have shown no changes in Rint, despite radiographic worsening (70) and changes in sRaw (39).…”
Section: Review Of Studies Conducted Inmentioning
confidence: 99%
“…There are several studies of Rint in children with CF (39,(65)(66)(67)(68)(69)(70), but only three involving children under 6 years of age (39,67,70). Although one study found a reasonable correlation between Rint and other lung function indices (sRaw, FEV 1 , FEF 25-75 ) (66), most studies have shown that Rint measurements do not distinguish health from disease, either at baseline (39,66,(68)(69)(70) or after BD (39,67,69). In addition, two longitudinal studies in 21 (70) and 30 (39) preschool children with CF and have shown no changes in Rint, despite radiographic worsening (70) and changes in sRaw (39).…”
Section: Review Of Studies Conducted Inmentioning
confidence: 99%
“…Interrupter resistance (Rint) is the ratio of pressure at the mouth measured after an occlusion and flow just before it [66]. Most studies in children with CF have shown that Rint does distinguish those from healthy controls and remains stable over time, despite other parameters indicating worsening disease [45,67]. Further reports will help define the role of these alternative tests in monitoring early CF lung disease.…”
Section: Other Measures Of Preschool Lung Functionmentioning
confidence: 99%
“…While some studies of preschool children with CF have demonstrated marginally higher Rint than their healthy counterparts (46), most studies have shown that Rint measurements do not distinguish health from disease (40, 4750). In addition, no deterioration in Rint was noted in a longitudinal study despite radiographic worsening in preschool children with CF (49). Application of the interrupter technique is limited in CF as the mouth pressure and alveolar pressure are unlikely to have reached equilibration during the short occlusion time (typically 100 ms) in patients with airflow obstruction, leading to an underestimation of airway resistance (47).…”
Section: Lung Function Testing In Infants and Young Childrenmentioning
confidence: 99%
“…Chest radiograph scores have been used as surrogates for lung disease in studies following infants from diagnosis after detection by newborn screening (64, 65), with radiographic progression evident in 85% of children by age 5 years (64). In preschool children, chest radiograph scores worsen over 3 years despite stable lung function measured by the interrupter technique (49). However, mild structural changes that typify early CF lung disease in infancy are generally subtle on traditional chest radiography, which provides a two-dimensional representation of a complex three-dimensional structure.…”
Section: Imaging Of the Chestmentioning
confidence: 99%